Luteolin is an Effective Component of Platycodon grandiflorus in Promoting Wound Healing in Rats with Cutaneous Scald Injury - Wang L; Hu L; Peng Z; Cao H; Cao D; Long Y; Zou Z (Dove Medical Press, 2022)
Liang Wang,1,* Longjiao Hu,2,* Zhilian Peng,3 Honghong Cao,1 Danfeng Cao,4 Yiqin Long,4 Zhengyu Zou4 1Pharmacy Department, Traditional Chinese Medicine Hospital of Jiulongpo Distriction Chongqing, Chongqing, People's Republic of China; 2Pharmacy Department, Chongqing Jiulongpo People's Hospital, Chongqing, People's Republic of China; 3Administrative Department, Traditional Chinese Medicine Hospital of Jiulongpo Distriction Chongqing, Chongqing, People's Republic of China; 4Clinical Laboratory, Chongqing Jiulongpo People's Hospital, Chongqing, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhengyu Zou, Clinical Laboratory, Chongqing Jiulongpo People's Hospital, Chongqing, People's Republic of China, Email hulongjiao494@126.com Liang Wang, Pharmacy Department, Traditional Chinese Medicine Hospital of Jiulongpo Distriction Chongqing, Chongqing, People's Republic of China, Email askliang621129@126.comBackground: Platycodon grandiflorus could significantly improve the pathological results of cutaneous scald injury, reduce the release of inflammatory factors and promote angiogenesis. This study investigated the wound healing effect of luteolin, an active component of P. grandiflorus, on induced cutaneous scald injury in Sprague-Dawley (SD) rats.Methods: The protein expression levels of TNF-α and IL-6 were detected by ELISA. QRT-PCR was adopted to detect the expression of TGF-β 1 and VEGF. Histopathological changes of scald wounds were analyzed by hematoxylin-eosin staining. Cell viability and migration ability were detected by CCK-8 assay and scratch assay.Results: Both in vivo and in vitro experiments showed that luteolin promoted wound healing of cutaneous scald injury. Gene Oncology (GO) functional analysis and rescue experiments showed that endothelial nitric oxide synthase 3 (NOS3) was the critical target of luteolin in treating cutaneous scald.Conclusion: This study demonstrated that luteolin is an effective component of P. grandiflorus and is effective in the treatment of cutaneous scald injury.Keywords: Platycodon grandiflorus, luteolin, scald injury, nitric oxide synthase, network pharmacology